Two Naomis - Rhuday-Perkovich, Olugbemisola; Vernick, Audrey (New York : Balzer + Bray, 2016)
"Other than their first names, Naomi Marie and Naomi Edith are sure they have nothing in common, and they wouldn't mind keeping it that way. Naomi Marie starts clubs at the library and adores being a big sister. Naomi Edith loves quiet Saturdays and hanging with her best friend in her backyard. And while Naomi Marie's father lives a few blocks away, Naomi Edith wonders how she's supposed to get through each day a whole country apart from her mother. When Naomi Marie's mom and Naomi Edith's dad get serious about dating, each girl tries to cling to the life she knows and loves. Then their parents push them into attending a class together, where they might just have to find a way to work with each other--and maybe even join forces to find new ways to define family"--Front cover flap.
"Other than their first names, Naomi Marie and Naomi Edith are sure they have nothing in common, and they wouldn't mind keeping it that way. Naomi Marie starts clubs at the library and adores being a big sister. Naomi Edith loves quiet Saturdays and hanging with her best friend in her backyard. And while Naomi Marie's father lives a few blocks away, Naomi Edith wonders how she's supposed to get through each day a whole country apart from her mother. When Naomi Marie's mom and Naomi Edith's dad get serious about dating, each girl tries to cling to the life she knows and loves. Then their parents push them into attending a class together, where they might just have to find a way to work with each other -- and maybe even join forces to find new ways to define family" -- Front cover flap.
Keywords: Friendship -- Juvenile fiction; Girls -- Juvenile fiction; Stepfamilies -- Juvenile fiction; Friendship -- Fiction; Stepfamilies -- Fiction; Girls -- Juvenile fiction; Stepfamilies -- Juvenile fiction; Friendship -- Juvenile fiction